The Effect of Auditor Opinion, Solvency, Company Size, and Audit Tenure on Audit Delay in Manufacturing Companies - Gessela, Gesi; Jefri, Riny (Journal Economic Business Innovation, 2024)
This research aims to test and analyze the influence of audit opinion, solvency, company size, and audit tenure on audit delay. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. This research uses quantitative methods with multiple linear regression analysis tools. The sampling method used purposive sampling with a total sample of 86 companies during 2017-2021. The results of this research show that partially audit opinion and company size have a positive effect on audit delay, while solvency and audit tenure have no effect on audit delay.